Positive feedback between partitioning of carbonyl compounds and particulate sulfur formation during haze episodes - H.Q. Shen; L.B. Huang; X. Qian; X. Qin; Chen, Z. M. (Environmental Science & Technology, 2024)
Carbonyl compounds are important precursors of aqueous aerosols in the atmosphere, while their gas-particle partitioning behaviors and roles in particulate sulfur formation are poorly understood. In this study, we investigate the partitioning of five carbonyl compounds (formaldehyde, acetaldehyde, acetone, glyoxal, and methylglyoxal) during haze episodes in Beijing, China. On haze days, the values of field-derived effective Henry’s law coefficients (KHf) on aerosols for these carbonyl compounds are 106–108 M atm–1, which are significantly higher (102–104 times) than those in pure water. Sulfate is observed to have a pronounced "salting-in" effect on these carbonyl compounds, resulting in at least 1-order-of-magnitude increase in their particle-phase concentrations. Parameterization schemes for their partitioning in the ambient aerosols were provided and applied to the multiphase chemical box model (RACM2-CAPRAM). When incorporated into the field-derived parametrization, the model significantly increased hydroxymethanesulfonate (HMS) production by 50-fold compared to using the parameters obtained in pure water, increasing from 2.6 × 10–2 to 1.23 μg m–3 h–1. The formed HMS can facilitate sulfate formation in turn through further oxidation by OH radicals and enhance aerosol hygroscopicity. These findings indicate a positive feedback loop between the partitioning of carbonyl compounds and particulate sulfur formation during haze episodes, providing new insights for controlling particulate pollution and reducing SO2 levels in urban areas.